A hydroponic vegetable business management approach in holistic good agricultural practices in Thailand - Ruploet, Ponkamon; Kaewhanam, Kathanyoo; Phansoomboon, Sayan; Piriyaphattarakit, Anan (Frontiers in Sustainability, 2024)
Good agricultural practices (GAP) are guidelines for farming to produce good-quality products that meet specified standards and make the most of resources. The objective was to study the problems and conditions of success in implementing a holistic system of good agricultural practices in hydroponic vegetable business management and strengthen the efficiency of the management of the safe agricultural standard system policy in Thailand. In this study, qualitative research methodology was used. The research was conducted using in-depth interviews, semi-structured interviews, and observations. Intermediaries and consumers in Thailand: there are 36 people. Data analysis was carried out using descriptive statistics. The results of the study revealed the problems and conditions for the implementation are government policies that are not conducive to implementation, and farmers lack the knowledge to put them into practice seriously. Farmers leading the implementation must understand and learn the methods. The first step is to ensure proper and safe farming standards. As a result, the knowledge gained can be used. This includes preparing and developing farmers, producers, and entrepreneurs to gain knowledge and produce quality agricultural products. To be a tool to control and promote products, managing agricultural production quality. Maintenance of post-certification standards: GAP for crops outlines policies, benchmarks, and audit processes that adhere to international standards. Suggestion: Cooperation from all pertinent sectors, from upstream to downstream, is necessary for the implementation of a sound agricultural practice system. to significantly improve Thailand's agricultural standards.